The role and mechanisms of myokines in sarcopenia: new intervention strategies for the challenges of aging - Cui, Xiangran; Liu, Hongfei; Liu, Yantong; Yu, Zhitong; Wang, Deyu; Wei, Wei; Wang, Shixuan (Frontiers in Medicine, 2025)
Sarcopenia is a major health issue among the global aging population, with a prevalence of 10 to 30% in those over 60 years old. As age advances, the gradual decline in muscle mass and function leads to reduced ability to perform daily activities and significantly increases the risks of falls, fractures, disability, and mortality. Recent studies have shown that skeletal muscle is not only a locomotive organ but also an important endocrine organ that affects systemic metabolism by secreting a series of bioactive molecules known as myokines. The secretion patterns of myokines undergo significant changes during aging and the progression of sarcopenia. Protective factors such as IL-15 and IGF-1 decrease, while pathological factors like myostatin and Activin A increase. This imbalance subsequently leads to the continued decline in muscle mass and function, reflected in multiple mechanisms including disruption of protein synthesis and degradation, mitochondrial dysfunction, and chronic inflammatory states. This article systematically reviews the role of myokines in sarcopenia, clarifies their molecular mechanisms, and explores clinical application prospects, aiming to provide a theoretical basis and new intervention targets for the prevention and treatment of sarcopenia. Future research should focus on the dynamic changes, interactions, and targeted intervention strategies of myokines to address the challenges of global aging and improve the quality of life for the elderly population.